(untitled) (Journal of the College of Education for Women, 2019)
Skills learning is considered as an important factor in learning any subject as well as mathematics . Mathematical skills have a number of steps that should be learned and understood faster and with more accuracy . The practical or applied skills are type of learning which includes educational preparation and hand on skills is acquired which conducted by organized educational institutions. The sample included (120) students (males and females) first year / dept.of electrical technigues . The mathematical skills are implemented to wire up the electrical circuts. Test is implemented with questions concerned with the skills .statistical operations were conducted as well as the validity and standard deviation for the test .The results showed a weak level of skill usage which was (48.3%) for students in field of wiring up the electrical circuts and reading the results on devices . The researcher concluded that the reason of the students weakness was the lack of experience of the students for the skill specially in practical side in past stages.